Integrating Information Technology and Reading Teaching to Promote the Development of Students’ Reading Ability - Sapra, Rekha (Journal of Educational Research and Policies, 2024)
A survey was conducted among students from Class VI to VIII at Sarpang Middle Secondary School to understand their perception of the reading culture at the school. The survey also aimed to evaluate the impact of a recent reading program initiative during morning hours on their reading habits and how the development of ICT helped them inculcate reading habits. One hundred students were selected through multi - stage sampling and responded to reading - related questions using a questionnaire. The survey was conducted both before and after the intervention, and data collected were analysed using descriptive statistics and frequency distributions. This systematic review examines how information and communication technology (ICT) is used to teach reading in the classroom and its effect on students' behaviour and motivation. The results showed that most students spent 30 minutes to 1 hour on reading, with books and text provided through technology. Students understood 80% of what they read, and their teachers were reported as their primary source of inspiration for reading. Additionally, all respondents felt that the reading program using ICT was helpful in the post - test survey. Lack of interest and lack of time were the two main constraints students faced in cultivating reading habits, with fiction and non - fiction books, both print and digital, dominating their interests. Overall, the recent intervention of introducing a reading program using both e - readers and library books significantly impacted students' reading habits, with some slight negative differences observed.